Caught in the middle?: Welfare state legitimisation and problematisation in german and swedish middle-class discourse - Barbehön, Marlon; Geugjes, Marilena (International journal of politics, culture and society, 2018)
When it comes to evaluating social and political developments, the category of the middle class takes a central position in public debates. The same holds true for welfare state research which assigns a vital role to the middle class, especially when redistributive measures have to be stabilised and legitimised. However, in these debates, it is largely overlooked that the middle class is an ambiguous concept which can bear a variety of meanings and argumentative functions. Against this background, this paper does not want to investigate what the middle class is, but rather how it gains meaning in discursive practices in different societies. Empirically, we compare German and Swedish media debates in regard to how meaning is attributed to the middle-class category as well as regarding the latter’s role in the legitimisation and problematisation of the welfare state. The analysis reveals that while in the German discourse the middle class’ well-being is considered to be the major aim of the welfare state and for the benefit of the whole society, the Swedish discourse is split into two threads: one which criticises the middle class for furthering social gaps and a second one which accuses the universal welfare state for constraining the autonomy of middle-class members. We argue that these differences between (and within) both discourses are due to different interpretive schemes which are anchored in the respective sociocultural context. The analysis thus demonstrates the additional value of an interpretive perspective which helps understanding the specific ways in which the welfare state becomes the object of political debate in different societies.
Gesehen am 24.01.2019